Diffusion Control on the Van der Waals Surface of Monolayers for Uniform Bi-Layer MoS2 Growth - Kim, Tae Soo; Noh, Gichang; Kwon, Seongdae; Kim, Ji Yoon; Dhakal, Krishna P.; Oh, Saeyoung; Chai, Hyun-Jun; Park, Eunpyo; Kim, In Soo; Lee, Eunji; Kim, Youngbum; Lee, Jaehyun; et al. (John Wiley & Sons Ltd., 2024)
2D MoS2 has gained attention for the post-silicon material owing to its atomically thin nature and dangling bond-free surface. The bi-layer MoS2 is considered a promising material for electronic devices due to its better electrical properties than monolayer MoS2. However, the uniform growth of bi-layer MoS2 is still challenging. Herein, the uniform growth of bi-layer MoS2 is demonstrated using gas-phase alkali metal-assisted metal-organic chemical vapor deposition (GAA-MOCVD). Thanks to enhanced metal reactant diffusion length in GAA-MOCVD, the uniform growth of bi-layer MoS2 film is achieved even at fast nucleation kinetics for a shorter growth time compared to previously reported MOCVD. The bi-layer MoS2 field-effect transistors (FETs) show superior electrical properties such as sheet conductance and electron mobility than monolayer MoS2 FETs. The electron mobility of bi-layer MoS2 FETs with bismuth contacts reaches a maximum of 92.35 cm(2) V-1 s(-1). Using the partially grown epitaxial bi-layer (PGEB) MoS2, it is demonstrated that a photodetector showed a near-infrared photoresponse with a low dark current that is advantageous for both monolayer and bi-layer applications. The potential expansion of the growth technique to layer-by-layer growth can result in boosted performance across a wide spectrum of electronic and optoelectronic devices employing MoS2.